UJI EFEKTIVITAS ECENG GONDOK (Eichhornia crassipes) DAN KAYU APU (Pistia stratiotes) SEBAGAI TUMBUHAN POLISHING TREATMENT UNTUK MENYISIHKAN BOD, COD, DAN TSS PADA LIMBAH CAIR RUMAH POTONG HEWAN - Nugraha Yudi Ananta; Bieby Voijant Tangahu (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2022)
The concentration of polluted materials contained in slaughterhouse wastewater such as BOD, COD, and TSS can have a negative impact on biota life, resulting in a negative impact on biota life. This study aims to treat slaughterhouse wastewater using the phytoremediation method with water hyacinth and apu wood so as to improve the quality of wastewater that will be discharged into water bodies. The main research was conducted in several stages, namely the propagation stage, acclimatization, range finding test, and main testing. The propagation stage is carried out for 1 month until shoots or second generation plants grow which will be used for the next stage. The acclimatization stage aims to get test plants that have adapted to the new environment. Then the range finding test stage must be carried out to determine the concentration of the test substance that will be used for the main test. The concentrations used are 0%, 5%, 10%, 20%, 40%, and 80% are carried out for 7 days. Then the main testing stage with the parameters analyzed are BOD, COD, and TSS. The result obtained at the range finding test stage show that in cattle slaughterhouse waste water hyacinth can live at a waste concentration of 10%. While apu wood can live at an effluent concentration of 20%. While the results of phytoprocessing show that in the liquid waste of slaughterhouses (cows) the most effective BOD removal in apu wood plants is 300.7 mg/L, the most effective COD removal in apu wood plants is 368 mg/L, and the most effective TSS removal in apu wood is 54.2 mg/L. In slaughterhouse liquid waste (chicken), the most effective BOD removal in apu wood plants is 65.4 mg/L, the most effective COD removal in apu wood plants is 176 mg/L, and the most effective TSS removal in apu wood is 76.8 mg/L.